Kajian Implementasi Kegiatan Tanggung Jawab Sosial Perusahaan Pertambangan (Corporate Social Responsibility) Terhadap Pemberdayaan Masyarakat dan Lingkungan - Suhardiman Gumanti; Restu Juniah; Ridhah Taqwa (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2016)
The basic principles of CSR (Corporate Social Responsibility) in line with the concept of mining management is good and right (good mining practices). Minerals including coal should be optimally utilized because it must be able to protect the functions of the environment and society. Referring to this, company should be able to provide increased prosperity to its stakeholders. That includes community involvement in mining activities that pay attention to the better direction of environmental quality. This study aimed to examine the CSR program of PT. Bukit Asam ( Persero ) Tbk. The relation of community based bokashi with the empowerment of people and the environment after mining activities were studied. Bokashi fertilizer production is likely to increase the income of the people, also, on the other hand the company will be facilitated with the supply of fertilizer to be used in the reclamation stage, especially for re-vegetation activities. This research is a descriptive study using survey methods to groups of people who produce bokashi fertilizer. Based on F test results obtained all the independent variables together have a significant impact on the community empowerment variables with calculated F value of 7.293 > 2.766 compared F table . The result of partial test (t test) found that the variable of interest CSR ( X1 ) and the issue of CSR ( X2 ) affect positively towards community empowerment with the t value respectively 2.780 and 2.797 > than t table of 2.002 . In terms of the environment empowerment of post-mining activities, it could be seen from the results of monitoring activities. It showed that percentage of plants growth were 76.56 to 97.80%, the highest number of plants growth was 1,140 plants / ha and the lowest number was 685 plants / ha.